Activin A target genes are differentially expressed between normal and neoplastic adult human testes: clues to gonocyte fate choice. (13th October 2018) - Szarek, M.; Bergmann, M.; Konrad, L.; Schuppe, H.‐C.; Kliesch, S.; Hedger, M. P.; Loveland, K. L.
Abstract: Background: Human testicular germ cell tumours (TGCT) arise from germ cell neoplasia in situ (GCNIS) cells that originate from foetal germ cell precursors. Activin A is central to normal foetal testis development, and its dysregulation may contribute to TGCT aetiology. Objective: (i) To test whether the expression profiles of activin A targets in normal and neoplastic human testes indicates functional links with TGCT progression. (ii) To investigate whether activin A levels influence MMP activity in a neoplastic germ cell line. Materials and Methods: (1) Bouin's fixed, paraffin‐embedded human testes were utilized for PCR‐based transcript analysis and immunohistochemistry. Samples ( n  = 5 per group) contained the following: (i) normal spermatogenesis, (ii) GCNIS or (iii) seminoma. CXCL12, CCL17, MMP2 and MMP9 were investigated. (2) The human seminoma‐derived TCam‐2 cell line was exposed to activin A (24 h), and target transcripts were measured by qRT‐PCR ( n  = 4). ELISA ( n  = 4) and gelatin zymography ( n  = 3) showed changes in protein level and enzyme activity, respectively. Results: (i) Cytoplasmic CXCL12 was detected in Sertoli and other somatic cells, including those surrounding seminoma cells. Anti‐CCL17 labelled only the cytoplasm of Sertoli cells surrounding GCNIS, while anti‐MMP2 and anti‐MMP9 labelled germline and epithelial‐like cells in normal and neoplastic testes. (ii) Exposing TCam‐2 cells to activin A (50 ng/mL) elevated MMP2 and MMP9 transcripts (fourfold and 30‐fold), while only MMP2 protein levels were significantly higher after activin A (5 ng/mL and 50 ng/mL) exposure. Importantly, gelatin zymography revealed activin A increased production of activated MMP2. Discussion: Detection of CCL17 only in GCNIS tumours may reflect a change in Sertoli cell phenotype to a less mature state. Stimulation of MMP2 activity by activin A in TCam‐2 cells suggests activin influences TGCT by modulating the tumour niche. Conclusion: This knowledge provides a basis for understanding how physiological changes that influence activin/TGF‐β superfamily signalling may alter germ cell fate.